(untitled) (Human Factors in Design, 2023)
The aim of this article is to understand how Inclusive Design, Universal Design and Universal Design for Learning approaches are used to support the learning of children with Autism Spectrum Disorder in early childhood education. To this end, a systematic literature review was carried out. After the analysis, categories of similarities were generated using inclusive approaches. As a result, it was noted that there are still few studies that use Inclusive/Universal Design approaches in the educational field for this audience. Thus, this gap can be explored in multidisciplinary studies between designers and education professionals.